Praetor Formula as an Instrument of Conceptual Legal Thinking in Roman Private Law of the Pre-Classical and Classical Periods - N. V. Razuvaev; M. V. Tregubov (Теоретическая и прикладная юриспруденция)
The article discusses the formula, which is a means of fixing the claim in Roman private law of the pre -classical and classical periods. The nature and essence of the formula are quite little studied in the special legal literature. At the same time, most authors are limited to the general characteristic of the structure of the formulas, indicating that in the formulary process the documentary formula had the same meaning that in the legis actio were legitimate claims declared orally. According to the authors, the study of the formula should be based on the general laws of the evolution of Roman private law. The work proves that the emergence of the formula is an indicator of the transformation of associative-shaped legal thinking into a conceptual thinking, and the formula itself is an important tool for conceptual thinking used to construct subjective rights, as well as giving them formal certainty and legal force.